Role of HR in Corporate Governance: A Watchdog or a Bloodhound?. Issue 4 (October 2019) - Narendran, Rajeshwari
Abstract: The image of a human resource (HR) professional in the eyes of employees and management revolves mostly around a 'generalist profile', busy in event management or ready to put bottlenecks for any of the issues and challenges with employees or workers alike. Mostly, it sounds like a bloodhound when HR is negatively ready to be a troublemaker rather than a problem-solver. Can HR play a vital role in being the catalyst of change? This article dwells upon seeing how the role of HR can be positive in fostering corporate governance.